Scientific and Organizational Activity of Jan Mydlarski - Stęślicka-Mydlarska , Wanda (Anthropological Review, 1985)
The article commemorates professor Jan Mydlarski, one of the outstanding Polish anthropologists, the organizer of anthropology in after-war Poland.